Impact of peak to average power ratio reduction techniques on Generalized Frequency Division Multiplexing for 5th generation systems. (October 2021) - Kumar, Pawan; Kansal, Lavish; Gaba, Gurjot Singh; Mounir, Mohamed; Sharma, Ashutosh; Singh, Pradeep Kumar
Abstract: Generalized Frequency Division Multiplexing (GFDM) is the advanced multi-carrier methodology proposed for a reliable operation of the 5 t h generation (5G) systems. It has been observed that the performance of GFDM is hampered by the elevated peak to power ratio (PAPR). High PAPR leads to the saturation of the transmit power amplifier which degrades the bit error rate (BER) and causes the out of band emissions. The prime objective of this work is to evaluate the PAPR performances of GFDM under the various reduction schemes like precoding, clipping, companding, precoding ＋ clipping and precoding ＋ companding. The results show that the precoding techniques combined with clipping or companding results in less PAPR and BER as compared to the conventional GFDM. The discrete cosine transform (DCT) and discrete sine transform (DST) precoded GFDM provides a signal to noise (SNR) improvement of 2 − 4 dB and 5 − 8 dB respectively, in comparison to conventional GFDM systems for a BER of 1 0 − 3 . Graphical abstract: Highlights: DCT and DST precoding can help in the reduction of PAPR in GFDM systems. Clipping and Companding (CC) are combined with precoding for greater impact. The performance of various PAPR reduction techniques are analyzed and discussed. Precoding techniques combined with CC resulted in less PAPR and BER.